Crèvecoeur's Eighteenth-Century Travels in Pennsylvania and New York - St. John de Crevecoeur, J. Hector, 1735-1813 (Book collections on Project MUSE., 1961)
Michel-Guillaume Jean de Crevecouer, long regarded as a chief figure in American letters of the Revolutionary period, is remembered as the author of Letters from an American Farmer and the posthumous Sketches of Eighteenth Century of America, but his last and most ambitious work has been almost entirely neglected. Published in France as Le Voyage dans la haute Pensylvanie et dans d'etat de New York, Crevecouer's last book was never popular and has not heretofore appeared in English. Yet the Voyage has much to add to Crevecouer's picture of eighteenth-century America, and to our own picture of.